La detección y traducción de las metáforas como herramienta didáctica en el aprendizaje de una L2 para alumnos de Bachillerato: Descripción frente a prescripción - Raúl Victoria Sánchez (Miscelánea: A Journal of English and American Studies, 2013)
In this article we will try to offer a perspective on the possible impact of the identification and translation of metaphors, found in newspaper articles written in English, on the L2 learning process of two groups of informants. These informants belong to two different groups of high school students, who are members of the same class, in the last two years of a secondary education School in Madrid (I.E.S. Gómez-Moreno), before the entry to University. They have identified and translated metaphors from two different perspectives: one group of informants, from a descriptive approach and another group from a prescriptive one. In our research we pursue two fundamental objectives: firstly, the estimation of the informants’ work from two different approaches about the identification of metaphors in newspaper articles, and secondly the assessment of the translations performed of the identified metaphors by each group of informants, from the approaches mentioned. The students’ work on the news articles published by The Times online and the collecting of data were carried out during an academic year (2009-2010), with both groups of informants. The news articles come from the opinion section of the newspaper and were collected between the 1st of January and the 30th of April in 2009.